Evidence for stress‐dependent mechanoreceptors linking intestinal biomechanics and sensory signal transduction. Issue 1 (15th August 2012) - Gregersen, Hans; Jiang, Wen; Liao, Donghua; Grundy, David
<x xml:space="preserve">Abstract</x> Sensory nerve endings are widely distributed throughout the body. Neither the nature of the mechanosensitive channels nor the principal mechanical stimulus for these receptors is known. Afferents supplying the gastrointestinal tract responding to distension and contraction are responsible for co‐ordinated reflex control, feeding behaviour and sensations, including pain. Different populations of intestinal afferent fibres follow different pathways to the CNS, have different terminal fields and possess different thresholds for activation that may reflect the extent to which mechanical forces are distributed and dissipated by non‐neural structures in the bowel wall. In this study, we have characterized the stimulus–response function of afferent fibres innervating the rat jejunum, correlating luminal distensions in the bowel wall with the firing frequency of mesenteric afferent nerve bundles. Combining video imaging with intraluminal pressure recordings and utilizing a strain softening protocol, we have determined whether mechanoreceptors respond primarily to stress or strain. Multiunit afferent recordings were separated using spike discrimination software into low‐threshold (LT) and high‐threshold (HT) single units. For multifibre afferent recordings and both LT and HT single units, we observed a linear relationship between circumferential stress and mesenteric afferent discharge that was independent of distension‐induced tissue softening, with correlation coefficients >0.9. A fivefold change in the rate of applied distension did not significantly alter the magnitude of the afferent response and the linearity of the stress‐dependent mechanotransduction in both multifibre preparations and the LT and HT afferent fibres (P > 0.2). Thus, the firing characteristics of intestinal mechanoreceptors are linearly associated with the input in terms of mechanical stress.